Butylated Hydroxytoluene Induced Resistance Against Botryosphaeria dothidea in Apple Fruit - Huang, Yan; Sun, Cuicui; Guan, Xiangnan; Lian, Sen; Li, Baohua; Wang, Caixia (Frontiers in Microbiology, 2021)
.Apple ring rot caused by Botryosphaeria dothidea is an important disease in China that leads to serious economic losses during storage. Plant activators are compounds that induce resistance against pathogen infection and are considered as a promising alternative strategy to traditional chemical treatment. In the present study, butylated hydroxytoluene (BHT), a potential plant activator, was evaluated for its induced resistance against B. dothidea in postharvest apple fruit. The physiological and molecular mechanisms involved in induced resistance were also explored. The results showed that BHT treatment could trigger strong resistance in apple fruit against B. dothidea, and the optimum concentration was 200 μmol L-1 by immersion of fruit. BHT treatment significantly increased the activities of four defensive enzymes and alleviated lipid peroxidation by increasing antioxidant enzyme activities. In addition, salicylic acid (SA) content was enhanced by BHT treatment as well as the expression of three SA biosynthesis-related genes (MdSID2, MdPAD4, and MdEDS1) and two defense genes (MdPR1 and MdPR5). Our results suggest that BHT-conferred resistance against B. dothidea might be mainly through increasing the activities of defense-related enzymes and activating SA signaling pathway, which may provide an alternative strategy to control apple ring rot in postharvest fruit.